Benefit‐Risk Summary of Regorafenib for the Treatment of Patients with Advanced Hepatocellular Carcinoma That Has Progressed on Sorafenib. (31st January 2018) - Pelosof, Lorraine; Lemery, Steven; Casak, Sandra; Jiang, Xiaoping; Rodriguez, Lisa; Pierre, Vadryn; Bi, Youwei; Liu, Jiang; Zirkelbach, Jeanne Fourie; Patel, Anuja; Goldberg, Kirsten B.; McKee, Amy E.; et al.
Abstract : : On April 27, 2017, the U.S. Food and Drug Administration approved regorafenib for the treatment of patients with advanced hepatocellular carcinoma (HCC) who had previously been treated with sorafenib. Approval was based on the results of a single, randomized, placebo‐controlled trial (RESORCE) that demonstrated an improvement in overall survival (OS). Patients were randomly allocated to receive regorafenib160 mg orally once daily or matching placebo for the first 21 days of each 28‐day cycle. The trial demonstrated a significant improvement in OS (hazard ratio [HR] = 0.63; 95% confidence interval [CI], 0.50–0.79, p  < .0001) with an estimated median OS of 10.6 months in the regorafenib arm and 7.8 months in the placebo arm. A statistically significant improvement in progression‐free survival (PFS) based on modified RECIST for HCC [Semin Liver Dis 2010;30:52–60] (HR = 0.46; 95% CI, 0.37–0.56, p  < .0001) was also demonstrated; the estimated median PFS was 3.1 and 1.5 months in the regorafenib and placebo arms, respectively. The overall response rate, based on modified RECIST for HCC, was 11% in the regorafenib arm and 4% in the placebo arm. The toxicity profile was consistent with that observed in other indications; the most clinically significant adverse reactions were palmar‐plantar erythrodysesthesia, diarrhea, and hypertension. Based on the improvement in survival and acceptable toxicity, a favorable benefit‐to‐risk evaluation led to approval for treatment of patients with advanced HCC. Implications for Practice: Regorafenib is the first drug approved by the U.S. Food and Drug Administration for the treatment of hepatocellular carcinoma that has progressed on sorafenib and is expected to become a standard of care for these patients. Abstract : Regorafenib is the first drug approved by the FDA for the treatment of hepatocellular carcinoma that has progressed on sorafenib and is expected to become a standard of care for these patients. This article summarizes the FDA's review of the data submitted in the supplemental New Drug Application and the basis for approval of regorafenib for this new indication.